2021
DOI: 10.3390/su13063193
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Corporate Performance and Bank Productivity in China: The Moderating Role of Independent Directors

Abstract: Corporate governance (CG) is not an abstract goal. It exists to serve the bank’s purpose by giving a framework through which investors, directors, and the top management can efficiently follow its objectives. Subsequently, it boosts the financial performance of the bank for its shareholders. This paper explores CG and its impacts on financial performance from the evidence collected from selected commercial banks (CB) in China. The data sample for this research comprises selected CBs in China for the period fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 72 publications
0
4
0
1
Order By: Relevance
“…Bank size is determined by taking the common logarithm of total assets some past investigations also used (Abdullah, 2005 ; Murtaza and Azam, 2019 ). Leverage measure as total obligations divided by total assets (Ilmas et al, 2018 ; Khan and Wang, 2021 ). Measurement of each variables are exist in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bank size is determined by taking the common logarithm of total assets some past investigations also used (Abdullah, 2005 ; Murtaza and Azam, 2019 ). Leverage measure as total obligations divided by total assets (Ilmas et al, 2018 ; Khan and Wang, 2021 ). Measurement of each variables are exist in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The statistical technique of Eviews was applied in the process of data analysis. To test the study hypothesis, we followed the FE model (Jensen and Murphy, 1990;Hermalin and Weisbach, 2006;Buck et al, 2008;Ausat, 2018;Khan and Wang, 2021 (1.1) Where i refers to the cross-section, t is time, and µ it is an error term. β 0 is the Constant coefficient of regression.…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Pada penelitian Horan & Mulreany (2021) menyimpulkan bahwa PAT bagi sebuah perusahaan memberikan kemampuan untuk mengikuti perubahan keterlibatan antar pemangku kepentingan meskipun literatur mengenai perusahaan sektor publik lebih berkembang ketimbang sektor swasta. Maka dari itu, literatur CG berdasarkan PAT dapat meningkatkan sumber pengetahuan bagi pembuat kebijakan dan regulator (Khan & Wang, 2021).…”
Section: Pendahuluanunclassified
“…Other scholars have explored banks’ management quality through the implementation of best corporate governance and social responsibility practices [ 24 , 51 53 ]. [ 51 ] applied different corporate governance practices in banks (i.e., female independent directors, CEO duality, and CEO shareholding) and found that bank financial performance was positively affected by these practices. [ 53 ] revealed that social responsibility and human resource management have a significant positive effect on bank reputation and a significant negative influence on turnover intention.…”
Section: Literature Reviewmentioning
confidence: 99%